KARAKTER MORFOLOGI DAN TIPE STELE TUMBUHAN PAKU TERESTERIAL DI HUTAN LINDUNG JUWATA KERIKIL KOTA TARAKAN SEBAGAI SUMBER BELAJAR BIOLOGI - Siska Siska; Marwiyah Marwiyah; Santi Santi; Hasdar Hasdar; Megita Aditiyanto (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
The goal of this resarch is to identify morphological characters and stele types of terestrial ferns in RPH Barat (Juata Kerikil) Forest. The result of research was analyzed the suitability to biology learning. This research used qualitative approach, and the sampling technique that was used was adaptive sampling. The result showed that the terestrial ferns consist of 12 species. Based on morphometri of frond, Overall, the ferns had many variety in the size. The largest one was Cyathea podophylla, and the smallest one is Trichomanes maximum. Next, Depend on stele type, majority of ferns have Dictyostele, nine of them have this stele type. In addition, the result related to Plant Taxonomy course and Plant Morphology course. Furthermore, the research related in Senior High School Curriculum (Curriculum 2013), especially in Plantae content. Keywords : Morphology, Stele, Terestrial Ferns